There Was an Old Lady Who Swallowed a Bat! - Colandro, Lucille; Lee, Jared (New York : Scholastic Inc., 2005)
Simple variations on the traditional cumulative rhyme.
Big book.
Keywords: Big books; Halloween -- Fiction; Bats -- Fiction